PENGUATAN KOMPETENSI GURU MELALUI ADMINISTRASI PENDIDIKAN: ANALISIS KONSEPTUAL DAN STRATEGI IMPLEMENTASI DI SEKOLAH - Hermawan, Farhan; Hafiedz, Kholid Abdul; Suklani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Improving teacher competence is a key factor in enhancing the quality of education and constitutes a systemic responsibility of educational institutions. This article aims to analyze the role of educational administration in strengthening teacher competence through policy management, program planning, academic supervision, and teacher performance evaluation in schools. This study employs a literature review method by examining various relevant sources, including academic books, nationally accredited journal articles, and educational regulations. The findings indicate that educational administration plays a strategic role in building a structured and sustainable system for teachers’ professional development. Core administrative functions such as planning, organizing, implementation, and supervision serve as the primary framework for directing teacher competence development. In practice, educational administration also utilizes principles of human resource management as operational instruments, particularly in teacher workforce planning, professional training, and performance appraisal. The challenges identified include budget limitations, managerial capacity of school leadership, weak collaborative culture, and suboptimal use of administrative data in decision-making processes. This article concludes that professionally and systematically managed educational administration represents a strategic approach to strengthening teacher competence and improving educational quality in schools.